Inflammatory monocytes promote progression of Duchenne muscular dystrophy and can be therapeutically targeted via CCR2 - Mojumdar, Kamalika (EMBO Mol Med, 2014)
Myofiber necrosis and fibrosis are hallmarks of Duchenne muscular dystrophy (DMD), leading to lethal weakness of the diaphragm. Macrophages (MPs) are required for successful muscle regeneration, but the role of inflammatory monocyte (MO)-derived MPs in either promoting or mitigating DMD is unclear. We show that DMD (mdx) mouse diaphragms exhibit greatly increased expression of CCR2 and its chemokine ligands, along with inflammatory (Ly6C(high)) MO recruitment and accumulation of CD11b(high) MO-derived MPs. Loss-of-function of CCR2 preferentially reduced this CD11b(high) MP population by impeding the release of Ly6C(high) MOs from the bone marrow but not the splenic reservoir. CCR2 deficiency also helped restore the MP polarization balance by preventing excessive skewing of MPs toward a proinflammatory phenotype. These effects were linked to amelioration of histopathological features and increased muscle strength in the diaphragm. Chronic inhibition of CCR2 signaling by mutated CCL2 secreted from implanted mesenchymal stem cells resulted in similar improvements. These data uncover a previously unrecognized role of inflammatory MOs in DMD pathogenesis and indicate that CCR2 inhibition could offer a novel strategy for DMD management.